2020
DOI: 10.3389/fphar.2020.586110
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Treatment for Refractory Epilepsies in Pediatrics

Abstract: Cannabis extracts in oil are becoming increasingly available, and, during the last years, there has been growing public and scientific interest about therapeutic properties of these compounds for the treatment of several neurologic diseases, not just epilepsy. The discovered role of the endocannabinoid system in epileptogenesis has provided the basis to investigate the pharmacological use of exogenously produced cannabinoids, to treat epilepsy. Although, physicians show reluctance to recommend Cannabis extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…Increasing the availability of CBD as adjunctive medication against severe forms of epilepsy, may in some cases provide significant benefits [6,9,27]. From the available studies in the pediatric population, synthetic cannabidiol oral solution can be considered safe at all doses tested and generally well tolerated in this population [5,10,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the availability of CBD as adjunctive medication against severe forms of epilepsy, may in some cases provide significant benefits [6,9,27]. From the available studies in the pediatric population, synthetic cannabidiol oral solution can be considered safe at all doses tested and generally well tolerated in this population [5,10,21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mandatory testing and a basic regulatory framework are also not required to define the area of indication, daily dose, route of administration, maximum recommended daily dose, packaging, shelf life and stability. Much of this inaccuracy stems from the fact that it is not legally regulated whether such products should be regulated as food, supplements or drugs [9,10].…”
Section: Legislationmentioning
confidence: 99%
“…Therapeutic use of cannabis in treatment of infantile spasms has been documented since 1840 but it was only in 2018 that cannabidiol (as Epidiolex marketed medicine) was approved by the FDA and then by the EMA as an add-on antiepileptic drug in children with Dravet syndrome and Lennox–Gastaut syndrome (serious epileptic encephalopathies, generally resistant to treatment). The efficacy of this treatment in reducing seizures frequencies and in improving the quality of life in childhood epilepsy was shown in recent systematic reviews and was summarised by Raucci et al [ 24 ].…”
Section: Pain and Role Of Cannabinoidsmentioning
confidence: 99%
“…Although the results of this study indicated that CBG at lower concentration compared to CBD showed the same antioxidant effects, CBD showed beneficial effects on neurotransmitter exocytosis, which was not observed in CBG, suggesting that CBD may be a more desirable therapeutic option. Currently, CBD is an FDA-approved treatment option against two rare and severe types of epilepsy including Lennox-Gastaut syndrome (LGS) and Dravet syndrome, in patients two years of age and older [122,123].…”
Section: Proteomic Studies On Other Cannabis-related or Derived Compoundsmentioning
confidence: 99%